EXTRACTION OF POTASSIUM FROM FELDSPAR AND LEUCITE BY TWO DIFFERENT ACTIVATION METH- ODS: MECHANICAL ACTIVATION (MILLING) AND HIGH TEMPERATURE ACTIVATION (ROASTING) - AGUS WAHYUDI; DESSY AMALIA; HADI PURNOMO (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2011)
One of the most important elements in fertilizers is potassium that can be devided from felsdpar and leucite minerals. Both are composed of various minerals and need to be separated from its impurities to get the desired minerals. In this research, test of mineral activation was performed using two different methods, namely mechanical activation (milling) and activation that used high temperature (roasting). The results were followed by potassium extraction process through leaching using sulfuric acid 6 N, 20% solids for 2 hours without heating. The best result was obtained from a 60-hour mechanically, activated leucite in leaching condition and conducted without heating. To evaluate potassium dissolution with soil when applied as fertilizer, the test of solubility in citric acid-the analogy of acid humus within soil-was conducted. The product with the best solubility was obtained from a 60-hour milling process. The results show that leucite, activated by milling process, was more easily extracted its potassium. However, further research is still needed to optimize the leachability of potassium extraction.